Honey Bee Tracheal Mite, Acarapis woodi (Rennie) (Arachnida: Acarina: Tarsonemidae) - Harold A. Denmark; Harvey L. Cromroy; Malcolm T. Stanford (EDIS)
In October 1984, the honey bee tracheal mite, Acarapis woodi (Rennie), was found in Florida. Although it was first described by Rennie in 1921, the mite was not found in the United States until 1984. Rennie described the mite from bees on the Isle of Wight and associated it with the "Isle of Wight" disease. Symptoms of this infestation were described as "bees crawling about unable to fly, and with wings disjointed; dwindling and mortality of colonies have been said to occur rapidly with colonies dying within a month." It was later shown that the tracheal mite was not the cause of the "Isle of Wight" disease (Bailey 1964), and later reports (Bailey 1968, Morse 1978) indicate that A. woodi is not as serious a pest of honey bees as previously thought. In combination with other adverse conditions, however, heavy mite infestations may cause a reduction in bee activity. This document is EENY-172 (originally published as DPI Entomology Circular 267), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.